A comparison of electrical characteristics of the Au/n-Si Schottky diodes with (ZnCdS:GO(1:1) and (ZnCdS:GO(1:0.5) doped PVP interlayer using current-voltage (I-V) and impedance-voltage (Z-V) measurements - Guclu, C. S.; Tanrikulu, E. Erbilen; Dere, A.; Altindal, S.; Azizian-kalandaragh, Y. (Springer, 2023)
In this study, both the Au/(ZnCdS:GO(1:1) doped PVP)/n-Si and Au/(ZnCdS:GO(1:0.5) doped PVP)/n-Si (MPS) type SDs which are named as SD1 and SD2, respectively, were fabricated onto the same n-Si wafer to determine effect of the rates of them using the I-V and C/G-V measurements. The basic electrical-parameters of them such as reverse-saturation current (Is), ideality-factor (n), barrier-height (phi B), rectification-ratio (RR), series/shunt resistances (RS, and Rsh) values, were calculated from the I-V data-based on thermionic-emission (TE) theory. The voltage dependence of surface -states profile was obtained from both the forward-bias I-V data (by considering voltage dependence of n, BH) and high-low frequency capacitance (CLF-CHF) methods for two SDs and were compared. These results indicate that SD2 has a lower leakage current and higher RR, Rsh, and BH than SD1 diode. On the other hand, the values of Nss with the same order (similar to 1012-1013 eV-1 cm2) for two SDs getting increases from the mid-gap of the semiconductor toward the bottom of the conduction band and change from region to region due to a particular density distribution of them in the bandgap. Both the voltage-dependent profile of Nss and Rs was also extracted from the C/G-V data by using Nicollian-Brews and high-low frequency capacitance method, respectively, and the values of them for SD2 are lower than the SD1 in the whole measured voltage range.
Keywords: Dielectric-Properties; Interfacial Layer; Different Rates; Ms Diodes; Parameters; Graphene; Zns